Layer by Layer. Interview with Andrea Éva Szőcs - Szabó, Zsófia (ARTCADIA, 2023)
Andrea Éva Szőcs DLA is a visual artist, associate professor at the Rippl-Rónai Art Institute of MATE Kaposvár, head of the Visual Department. Her art is versatile in its use of materials and techniques: from porcelain, bird feathers and razor blades to cotton candy, from graphics to installation and performance, she works with a variety of media to achieve her desired goal: to express thoughts. Her creations play with sign, meaning and perception, exploring the human mind through the correlation of forms, words and images. She examines points of view, builds on contrasts, and dresses her concepts in sensual materials. Her art has a strong impact on the senses, while stimulating thoughts and emotions – revealing the ambivalence and elusiveness of human nature.
Keywords: idea; installation; perception; metamorphosis; conceptualism